Use of a Dual-Antigen Rapid Diagnostic Test to Screen Children for Severe Plasmodium falciparum Malaria in a High-Transmission, Resource-Limited Setting. (24th August 2017) - Boyce, Ross; Reyes, Raquel; Matte, Michael; Ntaro, Moses; Mulogo, Edgar; Siedner, Mark J
Abstract : This prospective study examined the accuracy of a rapid diagnostic test (RDT) to distinguish severe from uncomplicated malaria. We found that a histidine-rich protein-2+/ pan -lactate dehydrogenase+ RDT result has high sensitivity (97.6%) for the detection of severe malaria and significantly outperformed existing algorithms. Abstract: Background: In rural areas, many patients with malaria seek care at peripheral health facilities or community case management programs. While this strategy is effective for the management of uncomplicated malaria, severe malaria necessitates prompt detection and referral to facilities with adequate resources. Methods: In this prospective, observational cohort study, we assessed the accuracy of a dual-band (histidine-rich protein-2/ pan -lactate dehydrogenase [HRP2/pLDH]) rapid diagnostic test (RDT) to differentiate uncomplicated from severe malaria. We included children aged <12 years who presented to a rural clinic in western Uganda with a positive HRP2 or HRP2/pLDH RDT. We estimated the test characteristics of a dual-antigen (HRP2+/pLDH+) band positive RDT compared to World Health Organization–defined clinical and laboratory criteria to detect severe malaria. Results: A total of 2678 children underwent testing for malaria with an RDT, and 83 (9.0%) satisfied criteria for severe malaria. The sensitivity and specificity of a HRP2+/pLDH+ result for severe malaria was 97.6% (95% confidence interval [CI], 90.8%–99.6%) and 75.6% (95% CI, 73.8%–77.4%), respectively. An HRP2+/pLDH+ result was significantly more sensitive (97.6% vs 68.7%, P < .001) for the detection of severe malaria compared to algorithms that incorporate screening for danger signs. Conclusions: A positive dual-antigen (HRP2/pLDH) RDT has higher sensitivity than the use of clinical manifestations to detect severe malaria, making it a promising tool in the triage of children with malaria in low-resource settings. Additional work is needed to operationalize diagnostic and treatment algorithms that include dual-antigen RDTs to avoid over referral.